PENINGKATAN PEMAHAMAN PAJAK BERBASIS WEB-GAMES ULAR TANGGA PAJAK PADA SISWA SEKOLAH MENENGAH KEJURUAN LETRIS - Agustine Dwianika; Augury El Rayeb; Siti Rahma Anggraini; Fiqkri Ardiyanto Nugroho; Elida Rahmawatie; Tasbita Fitria Sarwono; Arya Saraswati; Anita Pepbriani; Nuzul Rahmadani (Asosiasi Dosen Muda Indonesia, 2022)
Students' understanding of taxation can be achieved not only through print media such as textbooks or learning videos found on existing social media. The purpose of this community service activity is to provide a new way to increase the tax knowledge of Letris Vocational School students by playing online games (Web-Games) in the form of snakes and ladders on one of the sites provided. Web-Games is a technology that is used to play games using a device that is connected to an internet connection. This technology-based Community Service Activity (PkM) of Pembangunan Jaya University begins with a survey conducted by the team, coordinating the time and place of implementation, carrying out user requirements stages, and testing the tax snake ladder web games, and the final stage of evaluation. All stages went well although there was a time constraint on the participants' willingness to remember that the implementation was carried out during the school holidays. This PkM involves 52 Letris Vocational School students who are members of the Accounting Department and participate in the user requirements and socialization stages of this web game. The PkM team conducted a pre-test and post-test on respondents to increase their understanding of tax theory and practice. This comparison was carried out before and after the participants played the game manually and web-based. The results show that the participants' understanding of taxes increases both in terms of theory and practice of taxation in accordance with the provisions of generally accepted tax laws. The evaluation results show that this PkM activity is beneficial for partners, and needs to be expanded not only in one school but in a wider forum.